EDUKASI UPAYA PENINGKATAN PENDAPATAN DAN KESEJAHTERAAN PETANI DI DESA SEI ROTAN, KECAMATAN PERCUT SEI TUAN, KABUPATEN DELI SERDANG - Ahmad Fadlan; Annisa Ilmi Faried; Dinanti Dinanti (Smart Education, 2024)
Abstract: Income plays an important role in determining household expenditure, including family food consumption patterns. In Sei Rotan Village, wet-rice farmers face both internal and external challenges. The gap in access to modern technology in the agricultural sector is not only a technical issue, but also a social and economic issue that requires serious attention. This activity is expected to add insight into the interactive platform among participants, allowing the exchange of experiences and information among farmers, as well as facilitating discussions on important issues in local agriculture. The method used in community empowerment through Community Service activities by supervisors is in line with the Real Work Lecture by Universitas Pembangunan Panca Budi students. The success of this community service activity cannot be separated from the solid collaboration between supervisors, students, partners, and all members of the Sei Rotan Village community. Through this community service activity, the community can increase income from the agricultural sector and have an impact on improving the welfare of farmer groups. Keyword: income increase, agricultural digitallization